INOVASI PRODUK BASIC SAUCE DEMI-GLACE VEGETARIAN - Riana Dwi Putri; Anthony CA Arifin (Lembaga Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Pariwisata Bogor, 2022)
The background of this research was based on the search for substitutes for the main ingredients for making demi-glace which are usually animal-based, so that formulations were found that could replace the main ingredients for making demi-glace. The purpose of this product research is to obtain new products with vegan friendly base ingredients, make demi-glace more interesting or create new flavors in these products. It aims to find out whether people like demi-glace products with the formulation that the author made. The research method used in this study is a quantitative research method based on questionnaires that were tested and distributed to expert panelists as many as 20 people who are still active in the food and beverages industry who have tasted demi-galce products with new formulations, and the results are many from panelists gave 4 (very like) and 3 (like) marks to vegetarian demi-glace products.